Changes in Our Government’s Counterpart Support Policy, Logic of Evolution and Prospects for Reform: An Analysis based on Historical Institutionalism - Wang, Hanjing (International Journal of Social Sciences and Public Administration, 2024)
Coordinated regional development is inextricably linked to the practice of the counterpart support policy, and a scientific understanding of its historical process, evolutionary logic, and power mechanism is an important issue in realizing comprehensive economic and social progress and common prosperity. Based on the perspective of historical institutionalism, a panoramic overview of the internal logic of the change of the counterpart support system can help improve the foresight of reform. China’s counterpart support system has experienced three stages: early germination, initial establishment and deep promotion, and the reform process has been deeply influenced by the transformation of the economic system, the requirements of regional coordinated development and the consensus of community values, and has shown obvious path dependence. The birth of the "factory-package commune" model, the convening of the National Conference on Border Defence, and the speeches made at the conference on post-disaster reconstruction are three key points in the development of the counterpart support system. The power mechanism for the evolution of the counterpart support system comes from the vertical "administrative contracting system" and the horizontal "competition tournament". In the future, the counterpart support system will continue to develop along the lines of scientific, intelligent and balanced development, exploring new modes of counterpart support, and pushing forward the improvement of the quality and effectiveness of counterpart support work.